Gamble House : Building paradise in California - Bosley, Edward R.; Mallek, Anne E.; Scheid, Ann, 1940-; Winter, Robert; Vertikoff, Alexander ([California?] : The Gamble House/USC School of Architecture and CityFiles Press, 2015)
"For more than a century the Gamble House has stood on a promontory overlooking the Arroyo Seco, a thin riverbed that meanders down from the San Gabriel Mountains through Pasadena, California. For much of that time the house has been open to the public. More than a million visitors have toured the house since it became an architectural site in 1966. They come for a variety of reasons, but primarily to appreciate the uncommon mixture of art and craft that is the hallmark of architects Charles and Henry Greene. In the first publication about the house since its restoration in 2004, The Gamble House documents the history, design, craftsmanship, and enduring aesthetic impact of this renowned cultural landmark. New photography by Alexander Vertikoff illuminates a series of scholarly essays based on recently discovered archival materials."
Includes bibliographical references and index.
Keywords: David B. Gamble House (Pasadena, Calif.); Greene & Greene; David B. Gamble House (Pasadena, Calif.); David B. Gamble House (Pasadena, Calif.); Greene & Greene; Architecture, Japanese -- California -- Pasadena; Architecture, Domestic -- California -- Pasadena; Architecture japonaise -- Californie -- Pasadena; Architecture, Domestic; Architecture, Japanese; California -- Pasadena